2018
DOI: 10.1158/1078-0432.ccr-17-2885
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Exit Dysfunction through the Deregulation of APC/C Characterizes Cisplatin-Resistant State in Epithelial Ovarian Cancer

Abstract: Acquired resistance to cisplatin is a major barrier to success in treatment of various cancers, and understanding mitotic mechanisms unique to cisplatin-resistant cancer cells can provide the basis for developing novel mitotic targeted therapies aimed at eradicating these cells. Using cisplatin-resistant models derived from primary patient epithelial ovarian cancer (EOC) cells, we have explored the status of mitotic exit mechanisms in cisplatin-resistant cells. We have uncovered an unexpected role of long-term… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…3 D). These results are consistent with a previous observation showing mitotic exit vulnerability driven by Anaphase Promoting Complex/Cyclosome (APC/C) dysfunction in several cisplatin-resistant models of epithelial ovarian cancer 27 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…3 D). These results are consistent with a previous observation showing mitotic exit vulnerability driven by Anaphase Promoting Complex/Cyclosome (APC/C) dysfunction in several cisplatin-resistant models of epithelial ovarian cancer 27 .…”
Section: Resultssupporting
confidence: 93%
“…3D). These results are consistent with a previous observation showing mitotic exit vulnerability driven www.nature.com/scientificreports/ by Anaphase Promoting Complex/Cyclosome (APC/C) dysfunction in several cisplatin-resistant models of epithelial ovarian cancer 27 . On the other hand, String pathway analysis of carboplatin-survival genes for 468-R cells showed enrichment of the G2/M checkpoint components, G2 Checkpoint Kinase WEE1, Cell Division Cycle 7 (CDC7), and CHEK1 (Fig.…”
Section: The Mitotic Checkpoint Is Essential For Survival Of Carboplasupporting
confidence: 92%
“… 16 Resistance to conventional cisplatin therapy is attributed to populations of cancer stem cells that possess stem-like characteristics and high tumorigenicity. 17 It was well documented that the biology of ovarian cancer stem cells and identified various markers and signaling pathways for their self-renewal ability in recent years. Targeting cancer stem cells is the most prospective strategy to overcome ovarian cancer resistance and reduce mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Raab et al [82] reported that by eliminating the anti-apoptotic shielding through MCL-1 inhibition and blocking the activity of APC/C, the apoptosis-resistant and slippage prone HGSOCs were sensitized to the frontline therapy including paclitaxel. Belur Nagaraj et al [83] uncovered that longterm cisplatin treatment induced mitotic exit vulnerability in the presence of APC/C dysfunction along with cisplatin-resistance, where APC/C CDC20 inhibition increased the sensitivity of pharmacologic PLK1 inhibition, which in turn diminished cisplatin-resistant cell survival and aggravated spindle checkpoint response in cisplatin resistant ovarian cancer cells.…”
Section: Multi-subunit Ring E3 Ligase -Apc/cmentioning
confidence: 99%